Check sibling questions

Example 5 - Find m so that (-3)^m + 1 x (-3)^5 = (-3)^7 - Chapter 12 C

Introducing your new favourite teacher - Teachoo Black, at only β‚Ή83 per month


Transcript

Example 5 Find m so that γ€–(βˆ’3)γ€—^(π‘š+1) Γ— γ€–(βˆ’3)γ€—^5 = γ€–(βˆ’3)γ€—^7 γ€–(βˆ’3)γ€—^(π‘š+1) Γ— γ€–(βˆ’3)γ€—^5 = γ€–(βˆ’3)γ€—^7 γ€–(βˆ’3)γ€—^(π‘š + 1 + 5) = γ€–(βˆ’3)γ€—^7 γ€–(βˆ’3)γ€—^(π‘š + 6) = γ€–(βˆ’3)γ€—^7 Comparing powers m + 6 = 7 m = 7 βˆ’ 6 m = 1 (Using π‘Ž^π‘šΓ—π‘Ž^𝑛=π‘Ž^(π‘š + 𝑛))

Davneet Singh's photo - Teacher, Engineer, Marketer

Made by

Davneet Singh

Davneet Singh is a graduate from Indian Institute of Technology, Kanpur. He has been teaching from the past 12 years. He provides courses for Maths and Science at Teachoo.